Inventory of the herpetofauna of Talampaya National Park, a World Heritage Site in Argentina - Kass, Camila Alejandra (2018)
Talampaya National Park (TNP) was designated a UNESCO World Heritage Site, together with Ischigualasto Provincial Park in 2000, but there is no list with updated information from reptiles and amphibians eighteen years after its creation. Therefore, we listed a complete inventory of the herpetofauna of TNP with the information obtained from bibliography, data from Argentina National Parks Administration (ranger reports and the species listed in their database) and fieldwork using pitfall traps, active search transects and pictures/material collected in the site. We confirm the occurrence of 35 species of herpetofauna in the TNP, including 29 reptiles and 6 amphibians. Some species found in TNP are of great value because their national conservation status is vulnerable (Chelonoidis chilensis, Liolaemus anomalus, Liolaemus riojanus) or even endangered (Boa constrictor occidentalis). Therefore, priority areas for conservation of these species should be proposed inside the park.